Integrated Geophysical Study of the Collision Between the North China Craton and the Yangtze Craton and Its Links With Craton Lithospheric Thinning - Liu, Lihua; Hao, Tianyao; Lü, Chuanchuan; Wu, Zhiqiang; Kim, Kwanghee; Kim, Hanjoon; Xu, Ya (Frontiers in Earth Science, 2022)
Unlike stable cratons elsewhere in the world, the lithosphere is strongly thinned in the east of both the North China Craton (NCC) and the Yangtze Craton (YZC) compared with the west. We deployed four active-source onshore-offshore wide-angle seismic survey lines in the eastern NCC and YZC from 2010 to 2016 with the aim of revealing the mechanism of lithospheric thinning and the process of the collision between the NCC and YZC. We obtained high-resolution crustal P-wave velocity models for the eastern NCC and YZC based on seismic forward modeling, travel-time tomography and finite-difference wave-field modeling. Based on our integrated geophysical study and previous work, we propose a five-stage model for the collision between the YZC and NCC, with different dominant geodynamic mechanisms in each stage. Our collision model shows that lithospheric thinning in the eastern NCC and YZC is a consequence of the NCC-YZC collision and subduction of the Pacific plate.